Laparoscopy-guided Liver Abscess Drainage: An Additional Use of Veress Needle - Ekwunife, Christopher N. (Medknow Publications & Media Pvt Ltd, 2012)
Percutaneous image-guided drainage is the standard of care in the treatment of liver abscess. However this may not suffice in multi-loculated abscesses and those associated with concomitant biliary pathology. We report the case of a 34 year old male who presented to our hospital with a huge hepatic abscess that could not be aspirated percutaneously. Subsequently he had a laparoscopic guided aspiration of the abscess, with the aid of veress needle. Three weeks post operatively, no residual abscess cavity was noticeable. We believe that minimal access surgery techniques should always be considered in the management of liver abscess, and that the veress needle can be an additional aspiration device, in our environment.